Poster 243: Synovial Fluid MMP-1 and VEGF Concentration Correlates with Chondral Defects Severity and Symptoms in the Knee. Issue 7 (30th July 2022) - DeFroda, Steven; Trasolini, Nicholas; Zavras, Athan; Darwish, Reem; Cole, Brian; Yanke, Adam; Dandu, Navya
Objectives: The clinical significance of the concentration of inflammatory biomarkers in the synovial fluid of the knee has been studied in the context of several pathologies. However, there is a paucity of literature examining concentrations of synovial fluid inflammatory biomarkers in patients with focal chondral defects and their correlation with imaging findings. This study sought to explore the correlations between preoperative synovial fluid biomarkers, cartilage structural characteristics on MRI, and pre- and postoperative PROs in patients undergoing chondroplasty for focal chondral defects. We hypothesized that certain biomarkers within the synovial fluid would correlate with more severe grading of cartilage defects on MRI and have a negative relationship with patient reported outcomes. Methods: This study prospectively enrolled patients undergoing chondroplasty for symptomatic focal chondral defects of the knee. Prior to the initiation of arthroscopy, synovial fluid was aspirated from the operative knee. Multiplex ELISA was then performed on the supernatant for several analytes. The relationships between biomarker concentrations, demographic factors, MRI findings as measured by AMADEUS score, and pre- and postoperative PROs were explored via independent t -test or Pearson correlation analysis. Variables significant on univariate analysis were included for multivariate linear regression. Results: Cartilage defects of greater severity on MRI were significantly associated with increased concentration of MMP-1 and VEGF in synovial fluid (p<.05). Decreased preoperative KOOS Symptoms scores were correlated with increased concentrations of MMP-1 (r = -0.786, p<.001) and VEGF (r= -0.810, p<.001). These variables were non-significant on multivariate regression for KOOS Symptoms, although dominance analysis demonstrated that MMP-1 and VEGF were the greatest contributors to overall model fit, contributing 27.5% and 29.7%, respectively. Increased preoperative VEGF (r= -0.835, p=.019) and MMP-1 (r= -0.788, p=.036) were correlated with decreased improvement, or worsening of WOMAC stiffness score at 6 weeks after chondroplasty, while increased FGF2 (r=0.758, p=.049) and CCL2 (r= 0.777, p=.040) were positively correlated with improvement. Conclusions: This study demonstrated that the concentration of MMP-1 and VEGF in synovial fluid correlate with cartilage lesion severity and may correlate with patient function and symptoms. These inflammatory biomarkers may be an important target in clinical practice towards improving outcomes when managing chondral defects of the knee.